Tingkat Kecukupan Cadangan Kerugian Kredit Ekspektasian di Era Pandemi Pada Bank Pembangunan Daerah Bali - Santana, Dewa Ketut Wira; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2023)
The research aims to analyze the formation of Expected Credit Loss Reserves (CKKE) at the Bali Regional Development Bank (BPD) during the COVID-19 pandemic in accordance with POJK 17 of 2021 concerning the Second Amendment to Financial Services Authority Regulation Number 11/Pojk.03/2020 concerning National Economic Stimulus As a Countercyclical Policy on the Impact of the Spread of Coronavirus Disease 2019. The research uses a qualitative method approach with research subjects in all credit sectors owned by Bank BPD Bali. The methods used in collecting data in research are interviews and documentation studies. The data analysis technique used by the research uses triangulation, namely data reduction, data presentation, and drawing conclusions. The results of the study show that the level of adequacy of the establishment of BPD Bali's Expectation Credit Loss Reserves (CKKE) is in sufficient condition to be able to cover credit restructuring due to the impact of the COVID-19 pandemic, which can be seen from the average coverage ratio which has been 100%. Keywords: Banking, Credit Expectations, Economic Impactsiko debitur.